Inuvialuit Youth and Adaptation to Climate Change - Pearce, T; Smit, B; Ford, J D; Wandel, J; Lebourdais, M; Memogana, S; Kataoyak, F (2007)
Arctic communities have undergone rapid changes in the past half century. In recent years, communities have been exposed to additional stresses associated with climate change. These changes have transformed harvesting practices, community social networks, cultural and spiritual traditions, and have been linked to loss of identity and its associated social problems. In research conducted with the community of Ulukhaktok, Northwest Territories, Canada, community members identified specific concerns over the vulnerability of community youth. Adult community members and educators point to the potential loss of traditional land-based skills coupled with lack of workplace-relevant skills among the growing population of young Inuvialuit. For example, the role played by technology, globalization, and loss of language in conditioning how Inuvialuit youth experience and respond to climate change remains largely unexplored. In response to this community-identified research need, research is being undertaken in Ulukhaktok together with youth, elders and educators to identify how social change and climate change interact to affect the well-being of community youth, and to identify means for strengthening adaptive capacity. In previous research, youth expressed concerns including: lack of competency standards in education; limited employment; inadequate housing; drug and alcohol abuse; loss of language; and loss of traditional land-based skills. This research builds on these concerns and involves community youth in applied-participatory research through a host of methodological tools including: focus groups, participatory mapping, analysis of secondary sources, and the use of the Internet and video technologies. This paper describes the context for this new research and reports on preliminary findings.